Surgery Plus Chemotherapy Versus Surgery Alone for Limited-Stage Small-Cell Lung Cancer: A Population-Based Survival Outcome Analysis - Ye, Pingting; Guo, Zhuolin; Zhang, Yanfei; Dong, Chunyan; Li, Ming (Frontiers in Oncology, 2021)
Introduction: For patients with limited-stage small-cell lung cancer (LS-SCLC), effective treatment methods still remain a clinical challenge. The aim of this study is to evaluate the survival outcome of surgery plus chemotherapy vs. surgery alone in patients with LS-SCLC. Methods: LS-SCLC patients selected from the Surveillance, Epidemiology and End Results (SEER) database diagnosed between January 1, 2004, and December 31, 2015. Comparison of overall survival (OS) and cancer-specific survival (CSS) between two groups performed propensity score matching (PSM), inverse probability of treatment weight (IPTW), and overlap weighting analysis. Results: Of the 477 LS-SCLC patients identified from the SEER database between 2004 and 2015, 262 (54.9%) received surgery-plus-chemotherapy treatment and the others received surgery-alone treatment. Univariate and multivariate analyses showed that treatment option (P< 0.001), tumor location (P= 0.02) and AJCC stage (P< 0.001) were independent prognostic predictors of OS in LS-SCLC patients. Median OS was 35 months in surgery-plus-chemotherapy group vs. 23 months in surgery-alone group. Survival analysis showed that surgery plus chemotherapy offered significantly improved OS as compared with surgery-alone treatment before and after IPTW, PSM and overlap weighting method (all P< 0.05). According to AJCC stage stratification, OS of the unmatched patients with stage I (P= 0.05) and II (P= 0.001) SCLC who received surgery-plus-chemotherapy treatment was significantly better than that of surgery-alone patients. Conclusions: This cohort study showed that surgery plus chemotherapy was associated with longer survival time than surgery alone in LS-SCLC patients, especially in those with stage I SCLC. Further prospective studies are required to confirm our conclusions.